Laparotomy for Abdominal Stab Wound With Combined Omental and Organ Evisceration: 10-Year Experience From a Major Trauma Centre in South Africa. Issue 4 (April 2023) - Kong, Victor; Cheung, Cynthia; Rajaretnam, Nigel; Sarvepalli, Rohit; Xu, William; Bruce, John; Laing, Grant; Clarke, Damian
Introduction: Combined omental and organ evisceration following anterior abdominal stab wound (SW) is uncommon and there is a paucity of literature describing the management and spectrum of injuries encountered at laparotomy. Methods: A retrospective study was undertaken on all patients who presented with anterior abdominal SW involving combined omental and organ evisceration who underwent laparotomy over a 10-year period from January 2008 to January 2018 at a major trauma centre in South Africa. Results: A total of 61 patients were eligible for inclusion and all underwent laparotomy: 87% male, mean age: 29 years. Ninety-two percent (56/61) had a positive laparotomy whilst 8% (5/61) underwent a negative procedure. Of the 56 positive laparotomies, 91% (51/56) were considered therapeutic and 9% (5/56) were non-therapeutic. In addition to omental evisceration, 59% (36/61) had eviscerated small bowel, 28% (17/61) had eviscerated colon and 13% (8/61) had eviscerated stomach. A total of 92 organ injuries were identified. The most commonly injured organs were small bowel, large bowel and stomach. The overall complication rate was 11%. Twelve percent (7/61) required intensive care unit admission. The mean length of hospital stay was 9 days. The overall mortality rate for all 61 patients was 2%. Conclusions: The presence of combined omental and organ evisceration following abdominal SW mandates laparotomy. The small bowel, large bowel and stomach were the most commonly injured organs in this setting.